The Effect of the COVID-19 Pandemic on EPDS Scores and Maternal Quality of Life [A239]. (May 2022) - Twichell, Elizabeth; Zofkie, Amanda; Mathisen, Danielle; Lafferty, Ashlyn; McIntire, Donald D.; Morgan, Jamie
Abstract : INTRODUCTION: The COVID-19 pandemic has impacted mental health. We evaluated the impact on pregnant women and compared the Edinburgh Postpartum Depression Scale (EPDS) and a Maternal Postpartum Quality of Life Questionnaire (mPQOL) before and during the pandemic to evaluate the effect of the pandemic on maternal mental health and quality of life. METHODS: After institutional review board approval, EPDS screening exams and mPQOL surveys were collected postpartum on all pregnant women during six 12-week epochs prior to and during the pandemic (Epoch 1: December 16, 2019, to March 8, 2020; Epoch 2: March 9, 2020, to May 31, 2020; Epoch 3: June 1, 2020, to August 23, 2020; Epoch 4: August 24, 2020, to November 15, 2020; Epoch 5: November 16, 2020, to January 31, 2021; Epoch 6: February 1, 2021, to May 2, 2021). Scores were compared among the epochs. A score of 13 or higher indicated screening positive for depression. The mPQOL survey was evaluated by sub-categories: Psychological/Baby, Socioeconomic, Relational/Partner, Relationships/Family, and Health/Functioning. Satisfaction was ranked on a scale from 1 to 6 (1=very dissatisfied, 6=very satisfied). EPDS scores and mPQOL scores were compared among the epochs to determine contributors that impacted quality of life during the pandemic. RESULTS: Out of 2, 011 women, an EPDS score of 13 or higher increased from 3% to 9% from Epoch 1 to Epoch 2 and peaked at 11% in Epoch 5 ( P =0.007). mPQOL Socioeconomic and Relational/Partner sub-category scores decreased significantly from 5.8 to 5.5 ( P =0.014) and 5.5 to 5.4 ( P =0.041), respectively, from Epoch 2 to Epoch 3. CONCLUSION: There was a significant increase in positive EPDS screens in pregnant women during the COVID-19 pandemic. Sub-scores obtained from the mPQOL survey suggest that increasing socioeconomic concerns and relational partner issues may have driven these trends.